The role of protein-53 amyloid in determining the aggressiveness of basal cell carcinoma regulated by interleukin-6, myeloid cell leukemia-1 and basic fibroblast growth factor - Prasetyadi Mawardi; Handono Kalim; Kusworini Handono Kalim; Loeki Enggar Fitri; Karyono Mintarjo; Ambar Mudigdo; Oyong Oyong; Brian Wasita (PAGEPress Publications, 2019)
Basal cell carcinoma (BCC) is a common malignant skin tumor that rarely metastasized, although it is often locally destructive and aggressive. The amyloid in BCC is resulted from degenerated epithelial cell through apoptosis caused by activation of p53. Interleukin-6, MCL-1 and bFGF are inflammatory mediators which have important role in angiogenesis. To prove that high expression of p53 amyloid is related to aggressiveness of BCC via the regulation of IL-6, MCL-1 and bFGF expression. Archived specimens from 51 cases diagnosed with Primary BCC. We performed immunohistochemical staining for IL-6, MCL-1, bFGF expression and p53 amyloid deposit. There was a significant difference in the expression of p53 (p = 0.04), amyloid deposits (p = 0.015), P53 amyloid deposits (p = 0.038), IL-6 (p = 0.040), MCL-1 (p = 0.032), bFGF (p = 0.044) in A BCC compared with NA BCC. There were a significant association between MCL-1 and bFGF (p = 0.07) and p53 amyloid with bFGF (p = 0.051). p53 amyloid, IL-6, MCL-1 and bFGF have an important role in BCC aggresivity.